2018
DOI: 10.3389/fphar.2018.00895
|View full text |Cite
|
Sign up to set email alerts
|

Potential Metabolic Drug–Drug Interaction of Citrus aurantium L. (Rutaceae) Evaluating by Its Effect on 3 CYP450

Abstract: Aim: Fructus aurantii (FA) is widely used in clinic as an expectorant and digestant herb in traditional Chinese medicine and proven to have a variety of pharmacological functions. FA is close to grapefruit either by botanical taxonomy or by their same components (flavonoids, etc.) and grapefruit has been proven to cause drug–drug interaction when co-administrated with CYP3A4 substrates. Besides, FA contains many compounds, such as flavonoids, which have been reported to impact the expressions of CYP450. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“… 35 Moreover, a significant CYP3A4 and CYP1A2 induction was also observed in an in vivo animal study, showing a possible mixed effect on cytochromes. 36 Therefore, since large human clinical trials are still not available, caution should be exercised with the concomitant administration of C. aurantium derivatives and CYP3A4 metabolized drugs.…”
Section: Resultsmentioning
confidence: 99%
“… 35 Moreover, a significant CYP3A4 and CYP1A2 induction was also observed in an in vivo animal study, showing a possible mixed effect on cytochromes. 36 Therefore, since large human clinical trials are still not available, caution should be exercised with the concomitant administration of C. aurantium derivatives and CYP3A4 metabolized drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Water extract of FA immature increased CYP3A4 protein expression and ethanol extract of FA immature induced CYP3A4 expression via the induction of PXR expression [45]. FA may be a potential minor inducer of CYP1A2 and CYP3A4 [46]. Related research shows that resveratrol may interfere with albumin binding of site II ligands and metabolism of drugs by CYP2C9 and/or CYP3A4 enzymes [47].…”
Section: Resultsmentioning
confidence: 99%
“…GF inhibited intestinal and hepatic CYP3A4 in an exposure-dependent fashion, and patients taking CYP3A4 substrates are at risk of developing drug-related adverse events if consuming large amounts of GF . The GF-induced pharmacokinetic change of multiple drugs might be better explained by the impairment of CYP450 in the intestinal wall rather than in the liver. , In rats, FA upregulated the protein expression of CYP1A2, CYP3A4, and CYP2E1 and the mRNA expression of CYP1A2 and CYP3A4, which indicated that it might be a slight inducer of CYP1A2 and CYP3A4 . Besides, the extracts of FA and FAI showed mild inhibition on CYP3A .…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 In rats, FA upregulated the protein expression of CYP1A2, CYP3A4, and CYP2E1 and the mRNA expression of CYP1A2 and CYP3A4, which indicated that it might be a slight inducer of CYP1A2 and CYP3A4. 24 Besides, the extracts of FA and FAI showed mild inhibition on CYP3A. 25 UGTs were a series of enzymes responsible for conjugative phase II reactions of drugs.…”
Section: Discussionmentioning
confidence: 99%